PENGARUH METODE BERBEBAN TERHADAP KECEPATAN TENDANGAN SABIT PADA ATLET PENCAK SILAT UNIT KEGIATAN MAHASISWA UNIVERSITAS ISLAM RIAU - Kamarudin Kamarudin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2014)
Based on the writer’s observations in the field showed speed of Tendangan Sabit of Pencak Silat from Students Community Unit of Riau Islamic University was still low. This research aimed to know the influence weight method towards the speed of Tendangan Sabit of Pencak Silat from Students Community Unit of Riau Islamic University. This research method was an experimental research (a quasi-experimental). This research population were totally 13 athletes, whereas the samples were taken through total sampling so that it was got 13 male athletes. A test was used to find out the speed of Tendangan Sabit of Pencak Silat from Students Community Unit of Riau Islamic University. The Data obtained were analyzed using t-test. The Results of the analysis of the data indicates that weight method gives a significant influence toward the speed of Tendangan Sabit from Students Community Unit of Riau Islamic University since T-obs (5.839) was bigger than T-table (1.782). (3) It can be seen that weight method a significant influence toward the speed of Tendangan Sabit from Students Community Unit of Riau Islamic University.Key words: weight method, speed of Tendangan Sabit, Pencak Silat.